Effect of magnetron sputtering parameters on the performance of synthesized Fe/Co–N–C catalysts - Tengfei Li; Nongyang Yan; Quan Liu; Kun Wang; Zhengwei Wu (AIP Advances)
In this study, using magnetron sputtering technology, we successfully prepared Fe/Co–N–C thin film catalysts on the tip of a movable glassy carbon rotating disk electrode. By carefully adjusting the temperature, time, and power parameters during the preparation process, we synthesized three groups of catalysts with different characteristics. We undertook a thorough investigation to assess the influence of magnetron sputtering parameters on the electrochemical characteristics of the catalyst thin film, specifically designed for the oxygen reduction reaction (ORR). Our investigation involved a series of experiments, where we varied the temperature, time, and power settings to observe their effects on the catalysts’ characteristics and performance. The scanning electron microscopy examination revealed nuanced variations in the surface morphologies of the catalysts prepared under diverse parameters. To better comprehend the catalysts’ constitution and characteristics, we performed x-ray photoelectron spectroscopy analysis on a representative Fe/Co–N–C sample prepared at 600 °C for 60 min with a power setting of 20 W. The test results showed that the catalyst was rich in active nitrogen elements, and active sites such as C–N, Fe–N, and Co–N had significant catalytic effects on the ORR. The electrochemical performance testing results showed that the catalysts’ ORR performance exhibited a quadratic function trend with changes in experimental parameters. In particular, as the temperature, time, and power increased, the ORR performance of the catalyst gradually increased, reaching an optimal value before beginning to decrease.